2016
DOI: 10.1073/pnas.1614430113
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin DNA damage and repair maps of the human genome at single-nucleotide resolution

Abstract: Cisplatin is a major anticancer drug that kills cancer cells by damaging their DNA. Cancer cells cope with the drug by removal of the damages with nucleotide excision repair. We have developed methods to measure cisplatin adduct formation and its repair at single-nucleotide resolution. "Damage-seq" relies on the replication-blocking properties of the bulky base lesions to precisely map their location. "XR-seq" independently maps the removal of these damages by capturing and sequencing the excised oligomer rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
191
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(222 citation statements)
references
References 29 publications
(36 reference statements)
18
191
2
Order By: Relevance
“…It was also demonstrated that a positive correlation exists between DNA methylation patterns and mutations induced by UV irradiation (Willing et al, 2016). In addition, UV-C damages both euchromatin and heterochromatin whilst other genotoxic agents inducing bulky DNA lesions, like cisplatin, acts mostly in euchromatin (Hu et al, 2016). Therefore, all these parameters allow considering that, in addition to the presence of di-pyrimidines, DNA methylation, nucleosome density and histone variants/PTM may synergistically contribute to favor photolesions formation in heterochromatin vs euchromatin.…”
Section: Photolesions Are Sources Of Dna Methylation Changes In Hetermentioning
confidence: 98%
“…It was also demonstrated that a positive correlation exists between DNA methylation patterns and mutations induced by UV irradiation (Willing et al, 2016). In addition, UV-C damages both euchromatin and heterochromatin whilst other genotoxic agents inducing bulky DNA lesions, like cisplatin, acts mostly in euchromatin (Hu et al, 2016). Therefore, all these parameters allow considering that, in addition to the presence of di-pyrimidines, DNA methylation, nucleosome density and histone variants/PTM may synergistically contribute to favor photolesions formation in heterochromatin vs euchromatin.…”
Section: Photolesions Are Sources Of Dna Methylation Changes In Hetermentioning
confidence: 98%
“…Based on DNA sequence elements and histone posttranslational modifications, 15 chromatin states have been defined (35). In previous studies, we found that although these states did not affect cisplatin-induced damage formation, they did affect repair efficiencies, particularly in active promoters, enhancers, and transcribed gene bodies (10,13). We analyzed all 15 chromatin states for CPD, BPDE-dG, and (6-4)PP repair (Fig.…”
Section: Length Distribution and Nucleotide Frequency Analysis Of Excmentioning
confidence: 99%
“…We previously reported a method, termed excision repair-sequencing (XR-seq), for mapping nucleotide excision repair (6). This method has been used to generate excision repair maps for UV-induced cyclobutane pyrimidine dimers (CPDs) and (6-4)pyrimidine-pyrimidone photoproducts [(6-4)PPs], as well as cisplatin and oxaliplatin-induced Pt-d(GpG) diadducts for the human genome and CPDs for the Escherichia coli genome (10)(11)(12).…”
mentioning
confidence: 99%
“…2 The understanding of DNA damage response (DDR) and repair allowed the development of chemotherapeutical drugs to affect and defeat cancer cells, such as cisplatin and etoposide. 3,4 The different protein kinases related to the regulation of DDR and repair rely on a class of protein kinases: the NIMA-related kinases (NEKs) family. In general, NEKs have a conserved N-terminal catalytic domain, with approximately 40% amino-acid similarity, and a regulatory domain, which contributes to the uniqueness of each NEK protein.…”
mentioning
confidence: 99%